Lethal paralytic shellfish poisoning from consumption of green mussel broth, Western Samar, Philippines, August 2013 - Paola Katrina Ching; Ruth Alma Ramos; Vikki Carr de los Reyes; Ma Nemia Sucaldito; Enrique Tayag (World Health Organization Regional Office for the Western Pacific, 2015)
Background: In July 2013, the Philippines' Event-Based Surveillance & Response Unit received a paralytic shellfish poisoning (PSP) report from Tarangnan, Western Samar. A team from the Department of Health conducted an outbreak investigation to identify the implicated source and risk factors in coastal villages known for green mussel production and exportation. Methods: A case was defined as a previously well individual from Tarangan, Western Samar who developed gastrointestinal symptoms and any motor and/or sensory symptoms after consumption of shellfish from 29 June to 4 July 2013 in the absence of any known cause. The team reviewed medical records, conducted active case finding and a case-control study. Relatives of cases who died were interviewed. Sera and urine specimens, green mussel and seawater samples were tested for saxitoxin levels using high performance liquid chromatography. Results: Thirty-one cases and two deaths were identified. Consumption of >1 cup of green mussel broth was associated with being a case. Seawater sample was positive for Pyrodinium bahamense var. compressum and green mussel samples were positive for saxitoxin. Inspection revealed villagers practice open defecation and improper garbage disposal. Conclusion: This PSP outbreak was caused by the consumption of the green mussel broth contaminated by saxitoxin. As a result of this outbreak, dinoflagellate and saxitoxin surveillance was established, and since the outbreak, there have been no harmful algal blooms event or PSP case reported since. A "Save Cambatutay Bay" movement, focusing on proper waste disposal practice and clean-up drives has been mobilized.